The Effect of Civilian Unemployment on Reenlistment Decision in Turkish Armed Forces - Yıldırım Öcal, Jülide; Karasu, Şemsettin; GÜMÜŞOĞLU, NEBİLE KORUCU (My University, 2016)
The existing studies on the issue of reenlistment decision regard joining the army as a choice that an individual makes among alternative courses of action. Previous empirical research suggests that socio-economic background, higher educational benefits, civilian employment status and experience are among the determinants of reenlistment decision. This study investigates if unemployment has an effect on reenlistment decision of recruits for Turkish Armed Forces in a seemingly unrelated bivariate probit framework. Empirical analysis indicates that former civilian unemployment significantly increases the likelihood of reenlistment. Moreover, previous single equation models might be misspecified since the residuals of reenlistment and unemployment equations are correlated.
Keywords: Reenlistment; Unemployment; Turkish Armed Forces; Seemingly Unrelated Probit; İşsizlik; Türk Silahlı Kuvvetleri; Görünüşte İlişkili Olmayan Probit